2016
DOI: 10.1152/ajplung.00074.2016
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-to-mesenchymal transition in lipopolysaccharide-induced acute lung injury drives a progenitor cell-like phenotype

Abstract: Endothelial-to-mesenchymal transition in lipopolysaccharide-induced acute lung injury drives a progenitor cell-like phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 56 publications
(67 reference statements)
3
33
0
Order By: Relevance
“…Toshio Suzuki found that EndMT of pulmonary vascular endothelial cells is involved in the development of acute lung injury, partly mediated by ROS formation, and the process is closely affected by NAD(P)H oxidase-dependent ROS production 59 . The possible molecular mechanism, at least in part, is that oxidative stress increases the expression and secretion of TGFβ1 and TGFβ2 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Toshio Suzuki found that EndMT of pulmonary vascular endothelial cells is involved in the development of acute lung injury, partly mediated by ROS formation, and the process is closely affected by NAD(P)H oxidase-dependent ROS production 59 . The possible molecular mechanism, at least in part, is that oxidative stress increases the expression and secretion of TGFβ1 and TGFβ2 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study showed that one of the innate survival strategies for non-apoptotic injured PVECs is endothelial-to-mesenchymal transition (EndMT) [ 3 ], which is a process wherein endothelial cells lose an endothelial cell phenotype and acquire a mesenchymal cell phenotype [ 4 ]. There are many pathways, such as those that include the transforming growth factor β (TGFβ) superfamily, through which EndMT is induced [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that transient EndMT was observed in mice with septic acute lung injury (ALI) that can be repaired [ 3 ]. LPS-induced EndMT was reported to be dependent on ROS levels in vitro [ 6 ], and in vivo [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations